2020
DOI: 10.1016/j.scog.2020.100183
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bilateral high frequency repetitive transcranial magnetic stimulation on cognitive functions in schizophrenia

Abstract: Highlights Despite their major effects on positive symptoms, antipsychotics do not have a significant effect on cognition in schizophrenia Bilateral high frequency rTMS targeting dorsolateral prefrontal cortices has been effective on working memory Bilateral 20 Hz rTMS improved attention and verbal working memory in schizophrenia patients, It also improved the competence of switching the perceptional set up under a disruptive effect towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…2 . Eighteen studies showed a statistically significant superior effect of TMS compared to sham treatment 21 , 22 , 38 , 78 , 79 , 81 , 82 , 88 – 90 , 95 , 96 , 100 – 103 , 105 , 106 and one study found a statistically significant superior effect of sham treatment 36 . The remaining studies did not show a statistically significant difference between the treatment groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 . Eighteen studies showed a statistically significant superior effect of TMS compared to sham treatment 21 , 22 , 38 , 78 , 79 , 81 , 82 , 88 – 90 , 95 , 96 , 100 – 103 , 105 , 106 and one study found a statistically significant superior effect of sham treatment 36 . The remaining studies did not show a statistically significant difference between the treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…TMS is approved for the treatment of major depression (https:// www.accessdata.fda.gov/cdrh_docs/pdf6/K061053.pdf) and since the negative symptoms of schizophrenia and the symptoms of major depression both represent deficits of normal functions, TMS has also been explored as a potential treatment of negative symptoms among patients with schizophrenia [15][16][17][18] . Since the most recent reviews of the literature on TMS for treatment of negative symptoms [15][16][17][18] , several trials have been conductedsome using novel stimulation parameters as well as neuronavigation to improve targeting [19][20][21][22][23][24][25][26][27] . Due to these developments in the field, an updated synthesis would be of relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Standardized mean differences for the included studies are shown in Figure 2. Seventeen studies showed a statistically significant superior effect of TMS compared to sham treatment [13, 14, 34, 75, 76, 78, 79, 85-87, 91, 92, 96-99, 101] and one study found a statistically significant superior effect of sham treatment [32]. The remaining studies did not show a statistically significant difference between the treatment groups.…”
Section: Resultsmentioning
confidence: 99%
“…The means and standard deviations of PANSS-N was the most common missing piece of information (i.e., from studies where only the total PANSS scores were reported). From these 35 studies, three author groups provided data [13,18,31], and data were extracted from graphs in an additional eight studies [19,[32][33][34][35][36][37][38]. Hence, 24 articles were excluded due to non-available data .…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation